Satisfaction With Patient Engagement and Self-Reported Depression Among Hospitalized Patients: A Propensity-Score Matching Analysis - Xu, Richard Huan; Zhou, Ling-ming; Wong, Eliza Lai-yi; Chang, Jinghui; Wang, Dong (Frontiers in Psychiatry, 2022)
Background Depression is common among hospitalized patients and poses a significant threat to their quality of life. Patient engagement (PE) in healthcare has been shown to be associated with positive health outcomes. However, the relationship between PE and depression among hospitalized patients, with and without chronic conditions, has not yet been explored. This study aimed to investigate the association between patients’ satisfaction with PE and self-reported depression in Chinese public hospitals. Method A multi-centered, cross-sectional survey was conducted in seven tertiary-level public hospitals in Guangdong province, China. Twelve items from a patient-centered care questionnaire and the Patient Health Questionnaire 2-item version were used were used to assess patients’ satisfaction with PE and self-reported depression, respectively. Propensity score matching (PSM) approach was used to reduce selection bias and potential baseline differences between patients with and without chronic conditions. The relationship between satisfaction with PE and depression was assessed, using univariate and multivariate logistic regression analyses, respectively. Results A total of 1,974 hospitalized patients participated in the survey. After the PSM procedure, 604 patients were assigned to the chronic condition group, and another 604 patients were successfully matched in the comparison group with no differences in sex, age, educational level, and PE-related characteristics. Univariate logistic regression analysis indicated that high satisfaction with PE-related approaches significantly decreased the probability of developing depressive status. Multivariate logistic regression analysis further indicated that, after adjusting all PE-related approaches, “patient education” and “involvement in discharge planning” could significantly decrease the probability of patients developing depression. Conclusions Our results indicate that encouraging PE in clinical practice and improving patients’ satisfaction with PE interventions led to improved mental health outcomes among hospitalized patients in China.